Power of Attorney to Install Mortgages Made by Notaries in The Process of Charging Mortgage Guarantees on Ships - Arum Sekar Ayurani; Akhmad Budi Cahyono (LEGAL BRIEF, 2022)
The Mortgage Deed in the process of guaranteeing ship mortgages based on Law number 17 of 2008 concerning Shipping becomes the authority of the Registrar and Registrar of Ship Transfers (hereinafter referred to as P3BK). However, the mortgage deed product issued by P3BK is considered less protective and representative of the interests of the parties, namely creditors and debtors and has the potential to cause legal problems, it is necessary for a Notary to make a Power of Attorney to Install a Mortgage (hereinafter referred to as SKMH) using an authentic deed in accordance with Article 1171 of the Civil Code. The importance of making SKMH itself is basically to represent and protect the interests of the parties and as a means of reflecting the wishes of the parties. The existence of SKMH in the process of guaranteeing ship mortgages is the choice of the parties. The function of the SKMH made currently is not only used limitedly because the parties are in a different place from the registered ship, or because the parties are unable to be present at the time the guarantee binding is carried out, but the SKMH is made because it is desired by the parties in the Mortgage binding agreement to get more benefits. special protection that is felt to be able to bridge their desires that are not fulfilled by the P3BK mortgage deed.